Study on I-shaped section steel braces partially strengthened by induction heating. (1st May 2020) - Liu, Yuan; Tani, Masanori; Kurata, Masahiro; Watase, Chikai; Nishiyama, Minehiro
Highlights: An innovative type of I-shaped section steel brace partially strengthened by induction heating technology is developed. When the untreated normal-strength region yields, the induction-heated high-strength region can remain elastic before reaching large displacements. Therefore, the normal-strength region is able to exert the deformability, while the high-strength region maintains the load capacity. The preliminary experiment shows that the proposed induction-heated brace owns better structural performance in post-yielding behavior and strain dispersion after buckling compared to the conventional buckling brace. Abstract: Induction heating is an advanced technology to strengthen the selected region of steel materials. Recent advancement of the new treatment technique to partially strengthen large-scale steel components opens new research areas for civil engineering applications. This research explores the development of an innovative type of braces with the I-shaped section partially strengthened by induction heating. Therefore, when the normal-strength region of the brace enters the plastic stage, the induction-heated region can remain elastic before large deformations. This paper presents the design concept, numerical analysis, and the preliminary experiments on the proposed induction-heated braces, and finally clarifies the mechanism. The analysis results indicate that the induction-heated length and width greatly improve the tensile performances, and the larger induction-heated length relocates the hinge region after buckling, which is potential to stabilize the compressive behavior. The tensile coupon test results show that the yield strength and the tensile strength of the induction-heated region are raised up to 1.23 and 1.40 times of these of the normal-strength region. The preliminary experiments show that the proposed induction-heated braces succeed in achieving better tensile performances as well as reducing strain concentrations at the brace middle. However, the buckling loads of the induction-heated brace specimens are lower mainly due to the initial imperfections resulted from the induction heating process.